AUTHENTIC MATERIALS: TEACHERS’ PERCEPTIONS AND WHY THEY MATTER - zakky yavani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2017)
Abstract: The goal of learning English language in a class is to demonstrate the use of the language in real life application. Hence, the teaching and learning process must reflect, in such away, fits the reality. This calls for the use of real materials or authentic materials (AM) in the teaching and learning process. Though the positive result has been yielded by many researchers, the implementation of AM in teaching and learning English is not implemented fully in EFL setting. This research is conducted to investigate how teachers’ perception toward the use of authentic material in teaching and learning process. In depth - interview toward eight EFL school teachers, observation and documentation toward 4 English teachers are done to get the necessary data. In addition, focused group discussion (FGD) is done to triangulate the data. The finding showed that teachers perceived the important use of AM. Yet, they mostly fail to define what is AM and how it is implemented in the classroom. Their perception and action somehow do not match revealing a conclusion that they don’t’ fully understand what is AM; moreover the misconception of why it should be implemented matter the most. Keywords: Authentic Materials (AM), EFL School teachers, teachers’ perception